Características clínicas, epidemiológicas y de neuroimágenes de pacientes con diagnóstico de hemorragia subaracnoidea - Rojas Ramírez, Frank Lenin (2014)
Subarachnoid hemorrhage (SAH) is a type of hemorrhagic stroke caused by the rupture of a vessel directly into the subarachnoid space; the aneurysmal SAH occurs in the anterior communicating artery (36%), middle cerebral (26%), posterior communicating (18%) and internal carotid artery (10%). Risk factors involved in its etiology are: hypertension, smoking, alcoholism, family history. The symptomatology is characterized by the triad of sudden headache, vomiting and stiff neck. The most common complications are rebleeding, vasospasm, hydrocephalus, cerebral edema and intracranial hypertension. By Hunt-Hess scale of the severity of the condition and modified Fisher scale, the risk of vasospasm is quantified. Computed tomography is the most sensitive diagnostic test, you should practice as soon as possible, because with the passage of days decreases its sensitivity. Methods: A study Description- Transversal was conducted. We analyzed the medical records of all patients hospitalized with a diagnosis of subarachnoid hemorrhage seen at the Neurology Department of the Regional Hospital of Trujillo in the period 2009-2013. To obtain data token data collection was used, which comprised three aspects: clinical, epidemiological and neuroimaging characteristics. Results: 103 cases, of which only 86 met the selection criteria were studied, The 67.44% were female and 32.56% male. The ages ranged between 15 to 83 years, the average age of women was 53.06 years and 46.57 years for males. 54.65% had hypertension, diabetes mellitus 8.14% and 6.98% type 2 hypercholesterolemia. As was found harmful habits: drinking coffee (16.28%), snuff (4.65%) and alcohol (11.63%). At 72.09% were given medical discharge with "state of improvement." The symptoms of Entry: headache predominated in 100%, 75.58% vomiting. As for the location of the aneurysm, the 42.22% were found in the anterior communicating artery; 13.33% in the middle cerebral artery; 13.33% in the posterior communicating artery and 37.78% of aneurysms in the internal carotid artery. Conclusion: The Subarachnoid hemorrhage affected mostly women. The overall mean age was 51 years. Headache as the initial symptom, was present in 100% of patients, followed by vomiting 75.58% and 5.81% sentinel headache. The mortality rate was 11.63%. The severity assessed with the Hunt & Hess scale, grade II predominance (44.19%). The risk of delayed cerebral ischemia, prevalence of grade IV with 40.02% of the total. In case of aneurysms, the predominant size was medium (43.24%). The most frequent location was the anterior communicating artery (42.22%). Was predominantly saccular with 91.18% of cases